Inherited metabolic disorders among Turkish children with intellectual disability: A single-center experience - Bektas, Gonca; Ersoy Olbak, Melike; Uyanik, Bulent; Demet Kaya Ozcora, Gul (Annals of Medical Research, 2021)
Aim: We aimed to determine the frequency of inherited metabolic disorders (IMD) among Turkish children with intellectual disability using laboratory tests for IMD.Materials and Methods: Children older than 5 years of age with intellectual disability admitted to the Pediatric Neurology Outpatient Clinic for any neurological symptom between July 1, 2018, and December 31, 2018 were analyzed. Children with intellectual disability of unknown etiology at admission were included in the study. Complete blood count, serum biochemical analysis, thyroid function tests, serum ammonia, lactate, homocysteine, biotinidase activity, serum amino acids, acylcarnitine profile, and urine organic acid analysis results were evaluated.Results: A total of 163 patients (108 boys) were included in the study. The female to male ratio was 1: 2. The ages of the patients were between 5 and 17 years and the mean age was 9.4 ± 3.6 years. Four patients were diagnosed with IMD. Two of them had mitochondrial disease, 1 of them had isovaleric acidemia, and 1 of them had 3-Methylcrotonyl-CoA carboxylase deficiency. The accompanying symptoms of intellectual disability were psychiatric symptoms, dysarthria, ataxia, tremor and seizure in children diagnosed with IMD. We found that the percentage of IMD was 2.5% among Turkish children with intellectual disability.Conclusion: In our study, all IMDs identified in children with intellectual disability were treatable. That result emphasizes the significance of evaluating children for inherited metabolic disorders among children with intellectual disability.
Keywords: Brain disease; child; metabolic